2022
DOI: 10.1158/1078-0432.ccr-22-0112
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Activity of PolyPEPI1018 Combined with Maintenance Therapy in Metastatic Colorectal Cancer: an Open-Label, Multicenter, Phase Ib Study

Abstract: Purpose: Although chemotherapy is standard-of-care for metastatic colorectal cancer (mCRC), immunotherapy has no role in microsatellite stable (MSS) mCRC, a "cold" tumor. PolyPEPI1018 is an off-the-shelf, multi-peptide vaccine derived from 7 tumor-associated antigens (TAAs) frequently expressed in mCRC. This study assessed PolyPEPI1018 combined with first-line maintenance therapy in MSS mCRC patients. Experimental Design: 11 patients with MSS mCRC received PolyPEPI1018 and Montanide ISA51VG adjuvant subcutaneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Ultimately, there were no serious side effects from the vaccine, five patients got a single dose of PolyPEPI1018 and six patients got up to three doses every 12 weeks. Three patients progressed, five patients were stable, and three patients had partial tumor remission, two of whom had tumors that were small enough to undergo surgery (30). This is an advancement for MSS-CRC.…”
Section: Existing Mainstream Immunotherapy For Crcmentioning
confidence: 97%
“…Ultimately, there were no serious side effects from the vaccine, five patients got a single dose of PolyPEPI1018 and six patients got up to three doses every 12 weeks. Three patients progressed, five patients were stable, and three patients had partial tumor remission, two of whom had tumors that were small enough to undergo surgery (30). This is an advancement for MSS-CRC.…”
Section: Existing Mainstream Immunotherapy For Crcmentioning
confidence: 97%
“…For example, B16F10 CD133+/CD44+CSCs vaccine can effectively inhibit melanoma growth in mice and reduce the CSC population within tumors [ 97 ]. Although no cancer stem cell vaccine has entered clinical trials at this time, the demonstrated efficacy of a vaccine targeting metastatic CRC is reassuring and raises hope [ 98 ].…”
Section: Agents Targeting Cr-cscsmentioning
confidence: 99%
“…Another recent phase IIb clinical study was based on the multi-peptide vaccine PolyPEPI1018 (clinical trial identi er: NCT03391232) to induce T-cell responses against cancer testis antigens expressed in colorectal tumors [127]. The extended period of median PFS was 12.5 months in multiple vaccination recipients compared with a single dose [127].…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“…Another recent phase IIb clinical study was based on the multi-peptide vaccine PolyPEPI1018 (clinical trial identi er: NCT03391232) to induce T-cell responses against cancer testis antigens expressed in colorectal tumors [127]. The extended period of median PFS was 12.5 months in multiple vaccination recipients compared with a single dose [127]. Using in vitro stimulated ELISpot assay that assessed the induced CD8 + and CD4 + T-cell response and hence recruitment of cytotoxic tumor-in ltrating lymphocytes to tumor region converting "cold" tumor into "hot" tumor (Table 2) [127].…”
Section: Cancer Vaccinesmentioning
confidence: 99%